2008
DOI: 10.1108/17410400810916053
|View full text |Cite
|
Sign up to set email alerts
|

The impact of process mapping on transparency

Abstract: Purpose -Process mapping is used to articulate the activities and procedures of business entities in a graphical way as pictorial images readily convey considerable information. The objective of this research is to provide evidence and a methodology to assist organizations in evaluating the early stages of their process mapping efforts. Design/methodology/approach -A review of literature identifies key characteristics of transparency (process visibility) related to process mapping. Quizzes and surveys are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 11 publications
3
28
0
9
Order By: Relevance
“…This is especially true in developing economies such as South Africa. Klotz, Horman, Bi and Bechtel [79] have found that all tender procedures that might benefit small businesses and enterprises must be administered with adequate transparency as a means of supporting the SMME sector. Dasanyaka and Sardana [80] have found that strategic partnerships between national and provincial Governments as well as academic institutions benefit the SMME sector in terms of producing workable plans of actions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This is especially true in developing economies such as South Africa. Klotz, Horman, Bi and Bechtel [79] have found that all tender procedures that might benefit small businesses and enterprises must be administered with adequate transparency as a means of supporting the SMME sector. Dasanyaka and Sardana [80] have found that strategic partnerships between national and provincial Governments as well as academic institutions benefit the SMME sector in terms of producing workable plans of actions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The final important paramedic decisions were plotted onto a process map, 12 in the order of when they would likely arise during a typical emergency call. The investigators came to consensus about the plotting of each decision.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transparency can contribute to providing more feedback on performed activities and can facilitate coordination by revealing interdependencies, support decision-making and enable improvements (Bauch, 2004;Økland et al, 2010). Hence, transparency can enable increased participation, and provides stakeholders with the ability and authority for decision-making (Klotz et al, 2008). Drucker and Maciarello (2009) call attention to the importance of the human factor of transparency with the following statement: "There are, indeed, some principles of organization.…”
Section: Operational Integrationmentioning
confidence: 99%